High school to college transition research studies - Hicks, Terence; Lewis, Chance W. (Chance Wayne), 1972- (University Press of America, Incorporated, 2015)
This book offers two uniquely designed sections that provide a mixture of quantitative and qualitative research findings surrounding a diverse group of college students. The authors provide readers with valuable findings on topics such as student/faculty interactions, academic/social integration, and college preparation.